An Nahl Group's Honey Sales Assistance Through E-Commerce Shopee - Abd Rohman Taufiq (Universitas Muhammadiyah Malang, 2023)
Electronic commerce (E-commerce) can be described as the process of meeting sellers and buyers to conduct a transaction via the internet. The advantages of using Shopee's e-commerce media make it easier for business actors to do marketing easily and cheaply, reach unlimited consumers and potential business growth in the future. MSME Madu An Nahl Group marketing uses a word of mouth system and only to the surrounding environment so they have not used digital/online marketing. The abdimas program assistance aims to provide knowledge and training to Madu An Nahl Group in creating an online store and how to apply it to online buying and selling activities at Shopee e-commerce. The method in this mentoring program uses the Asset Based Communities Development (ABCD) method by prioritizing the utilization of existing assets and potentials in the vicinity of the Madu An Nahl Group MSME. The results of the abdimas mentoring activities at MSMEs Maadu and Nahl Group have produced an online store in the Shopee application for each store member in the shopee application, which is used as a means of buying and selling production goods. The products that have been created are in the form of handicrafts such as home decor, dry seblak and other branded products that can be sold freely